Post-colonial agricultural participation in livelihood strengthening (Research, Society and Development, 2018)
Post-colonial agricultural initiatives, programmes and models in Nigeria are aimed at empowering rural farmers to better yields and productivity while creating employment at community level. It necessitates food security, quality domestic food production and improvement in general welfare and livelihood and the farmers. The post-colonial era in Nigeria has witnessed numerous agricultural programmes. Example includes but not the least, the National Accelerated Food Production Project (NAFPP) 1972, Agricultural Development Projects, ADPs 1975, the Accelerated Development Area Project ADAP 1982, and the Multi-state Agricultural Development Projects MSADP 1986. The application of PEA in AVM ensures that positive outcomes and productions are expected through increase in farmers' awareness of modern technologies and practices. AVM is a multidisciplinary and multidimensional approach to improve the livelihood of rice farmers. Structured questionnaire and face to face interview were used to collect the data and SPSS was used to analyse the data. Human livelihood capital is characterized as a two-way thing, that is, it is concerned with both environmental influence on human life and human influences on the environment, focusing on the nature and quality of the relationship that exists between human communities and the ecosystem and how the environment provides the resource base for human existence. AVM prompted a shift from the usual way of financing farm projects to government involvement and providing farmers with information on how to secure loans, credit and financial incentives. Therefore, the study conclude that the introduction and adoption of AVM brought about substantial changes to the farmers livelihood capitals.